Analisis Kinerja Portofolio Optimal Saham Sektor Pertambangan dan Saham Sektor Perdagangan - ines ardelia; farida ratna dewi (Jurnal Manajemen dan Organisasi, 2016)
Stock Portfolio is a combination or a mixture of two or more individual stocks with the aim to minimize the risk. The importance of assessing the performance of a stock portfolio for investors will be valuable information for investment decisions. The purpose of this study was to analyze the condition of stock, stock performance, composition and combination of optimal stock portfolio formed in shares included Sectors and Stocks Trade Sector. Methods of data analysis used in this study is a model of Markowitz. Data research using quantitative secondary data during the period 2011 - 2015, obtained from IDX Statistic and Bank Indonesia website. The results showed that there are six stocks that are candidates portfolio, while the optimal portfolio is formed consisting of five stocks are share of UNTR, RALS, BIPI, MNCN and BMTR. The proportion of equity funds amounted to 52.48% UNTR, RALS amounted to 23.54%, Bipi amounted to 11.63%, MNCN amounted to 7.25%, and BMTR amounted to 5.10%.